2006
DOI: 10.3892/ijo.28.4.841
|View full text |Cite
|
Sign up to set email alerts
|

Survivin associates with cell proliferation in renal cancer cells: Regulation of survivin expression by insulin-like growth factor-1, interferon-γ and a novel NF-κB inhibitor

Abstract: Abstract. Although survivin has been widely recognized as an attractive target for cancer therapy, the exact mechanism regarding the regulation of survivin and its effect on cell proliferation have yet to be clearly defined in renal cell carcinoma (RCC). We investigated herein the association between survivin expression and cell proliferation in a RCC cell line, KU19-20. In KU19-20 cells, cell proliferation and survivin expression were significantly induced by IGF-1, whereas they were inhibited by a novel NF-κ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 22 publications
3
22
0
1
Order By: Relevance
“…Survivin has bi-functional roles; it drives cell division and inhibits apoptosis, as reported in renal cancer carcinoma 42 and lung cancer cells. 35 Furthermore, in vivo studies have suggested the role of survivin in the tumorigenesis of melanomas.…”
Section: Discussionmentioning
confidence: 95%
“…Survivin has bi-functional roles; it drives cell division and inhibits apoptosis, as reported in renal cancer carcinoma 42 and lung cancer cells. 35 Furthermore, in vivo studies have suggested the role of survivin in the tumorigenesis of melanomas.…”
Section: Discussionmentioning
confidence: 95%
“…An inverse correlation between XIAP expression and RCC aggressiveness has been reported [18]. High levels of Survivin correlated with poor survival in RCC patients [19], and siRNAs targeting survivin sensitized renal cancer cells towards chemotherapeutic agents and inhibited cell proliferation [20]. The expression of Smac, an endogenous inhibitor of IAPs, was down-regulated in RCC and inversely correlated Research Article with tumor stage and grade.…”
Section: Discussionmentioning
confidence: 96%
“…Survivin and XIAP are both important antiapoptotic proteins in renal cancer. Survivin has been reported to be associated with the proliferation of renal cancer cells (17) and is a potential molecular target for treating renal cancer (18)(19)(20). On the other hand, XIAP has been shown to be a prognostic marker in renal cancer (21).…”
Section: Discussionmentioning
confidence: 99%